High tick abundance and diversity of tick-borne pathogens in a Finnish city - Tero Klemola; Jani J. Sormunen; Janka Mojzer; Satu Mäkelä; Eero J. Vesterinen (Springer, 2022)
The sheep tick Ixodes ricinus is the primary vector for various zoonotic diseases, including Lyme borreliosis and tick-borne encephalitis (TBE), in Europe. Because both abundance of ticks and prevalence of tick-borne pathogens in these organisms have increased in many locations and under different environments, we designed a study to survey the occurrence of ticks and pathogens in an urban area, namely, the city of Turku, in SW Finland. In summer 2017, we collected >700 ticks, primarily from city parks, suburban forest patches, and recreational areas. Comprehensive subsets of ticks were screened for presence of all common tick-borne pathogens. Half of the ticks carried at least one pathogen. The most common pathogens detected were the causative agents of Lyme borreliosis, i.e., bacteria belonging to the Borrelia burgdorferi sensu lato group. Their prevalence was 37% in nymphal and 47% in adult ticks, which are high in comparison with surveys conducted elsewhere in northern Europe. Similarly, Rickettsia spp. (primarily R. helvetica) were also detected in a relatively high proportion of the samples (11% of both nymphs and adults). The TBE virus was not found in a relatively small subsample, but we detected (albeit at a low prevalence of 0–6% of nymphs and adults) the bacterial pathogens Borrelia miyamotoi, Anaplasma phagocytophilum and Candidatus Neoehrlichia mikurensis and the protozoan Babesia spp., which are also known agents of zoonotic diseases. The relatively high abundance of ticks and high diversity and overall prevalence of tick-borne pathogens suggest a lively and dense presence of mammalian and avian tick hosts in the city. Our results indicate a higher risk of encountering tick-borne pathogens in urbanized areas of southern Finland than previously known. Moreover, the possibility of acquiring tick-borne diseases from urban environments likely exists throughout most of Europe, and it should be acknowledged by health care professionals.